The effect of rainfall centroid position on lead time in the upstream Citarum River - Ode Asri Aristi Ayuningsi; Rohmat Faizal Immaddudin Wira; Kardhana Hadi (BIO Web of Conferences)
Flood early warning systems (FEWS) are essential for flood risk, particularly in flood prone areas such as Majalaya and Sapan in the Upper Citarum River (UCR). The primary objective in the development of a FEWS is to accurately predict the lead time. This study hypothesized a positive correlation between the distance of the rainfall centroid and lead time. To analyse this hypothesis, using Global Satellite Mapping of Precipitation (GSMaP) data, observation rainfall data, water level, and discharge processed using R Studio. Rainfall centroid is extracted from the raster data and corrected with rainfall correction to obtain the rainfall centroid point. The result is the effect of rainfall centroid, and the lead time differences in this case cannot be proven. The findings suggest that the spatial and temporal distribution of rainfall is highly random. The analysis revealed that, at any given moment, the rainfall centroid is consistently situated at the centre of the Majalaya and Sapan watersheds. Although the proposed hypothesis does not fully match the results, this finding provides new insights into the rainfall centroid and underscores the need for further study to understand the factors that influence the lead time for the FEWS.